BUDAYA BELAJAR MATEMATIKA RAMAH ANAK UNTUK PENGUATAN KECAKAPAN KOLABORASI DI SEKOLAH DASAR - Novitasari, Meggy; Linda Heshinta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Child-friendly mathematics learning is urgent in strengthening collaborative skills. A child-friendly approach encourages students to engage in deep conceptual communication. Collaboration has become increasingly important due to rapid global changes. This study aims to: 1) describe the culture of students learning with mathematics teachers, 2) describe the culture of students learning with peers in mathematics, and 3) explore the culture of students' independent learning in mathematics. This is a qualitative-ethnographic study conducted at Muhammadiyah Elementary School in Surakarta City, Central Java, from March to June 2025. The research data include both primary and secondary sources. Research subjects consist of the principal, teachers, and fifth-grade students at the research site. Data collection methods include interviews, observations, and document analysis. The researcher served as the key instrument. Data validity was ensured through source and method triangulation. Data were analyzed inductively. The findings reveal: 1) the implementation of child-friendly strategies by mathematics teachers has transformed the student learning culture with teachers to become more active, reflective, and collaborative, thereby strengthening collaboration; 2) an enjoyable learning culture was developed through child-friendly approaches to support collaboration enhancement. The success of collaboration heavily depends on the teacher as facilitator, the provision of challenging tasks, and process-based assessment; and 3) child-friendly mathematics learning promotes a culture of independent learning and supports collaboration. The role of teachers and professional support are critical to sustaining the transformation of the collaborative learning culture.